Oops! (Economist, 1998)
Reports on the increasing appeal of object-oriented programming in the computer database industry. Explanation of the differences between object-oriented and relational databases and how object-oriented are better; The advantage of being able to handle video data, graphics, and animation just as rapidly as other information.